Cloud computing : 6th International Conference, CloudComp 2015, Daejeon, South Korea, October 28-29, 2015, Proceedings /: 6th International Conference, CloudComp 2015, Daejeon, South Korea, October 28-29, 2015, Proceedings. (2016) - Unknown
No abstract available